Thomas Merton and Therese Lenfoehr: The Story of a Friendship - Hart, Patrick 1926- (2013)
The article reviews the book "Thomas Merton and Therese Lentfoehr: The Story of a Friendship," by Robert Nugent.
Keywords: Lentfoehr, Thérèse, 1902-1981; Merton, Thomas, 1915-1968; Nonfiction; Nugent, Robert, 1937-2014; Thomas Merton & Therese Lentfoehr: The Story of a Friendship (Book); Rezension